SPATIAL CONSERVATION STRATEGIES FOR POTENTIAL HERITAGE AT KAMPONG KAUMAN SURAKARTA - Musyawaroh, Musyawaroh; Pitana, Titis Srimuda; Masykuri, Mohammad; Nandariyah, Nandariyah (Department of Urban and Regional Planning, Diponegoro University, 2018)
Kauman is one of the cultural heritage kampong in Surakarta which was developed when Paku Buwono III was building Masjid Agung (The Great Mosque) in 1757. Abdi dalem ulama (the religious servant courtiers), together with their santries (Islamic students boarding school), live around the mosque which later was developed into Kauman. The abdi dalem ulama wives are taught to produce batik by the palace where they evolved to be batik entrepreneurs and made Kauman be batik center at the point of time. Batik business went bankrupt and made the Kaumanâs old buildings get ignored, damaged, and dirty due to the less maintenance. Kaumanâs unique culture should be conserved to support the ongoing revitalization. The researchâs main discussion was aimed at identifying the potential of cultural heritage at Kauman Surakarta and what strategies that can be used to conserve it. It was an applied research with the rationalistic qualitative approach. The conservation aspects discussed are tangible heritage and intangible heritage which are supported by spatial analysis using satellite imagery and Arch-GIS. The result of the research shows that tangible heritage which needs to be conserved at Kauman is ancient kampong toponym and ancient buildings. Meanwhile, intangible heritage is in the forms of social, cultural, economic, and religious aspects. The difference of this research from other researches is the involvement of Kauman community in preserving their area.